THE ROLE OF MYTHOLOGY IN THE CULTURAL-HISTORICAL PARADIGM OF DEVELOPMENT - Тарас ТИМОШЕНКО (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The work explores the role of mythology in the formation of cultural values, and paradigmatic coordinates as the most stable form of reproducing socio-cultural experience, namely as a mechanism for regulating human behavior, which is relevant for any type of culture. It is considered that the basis of the mythological form of organization of individual and group experience constitute from a sensory-reflexive, contemplative and productive way of understanding the world, and the mechanism of regulation of human behavior consists in the inseparability of the paradigmatic nature of behavior and the justification of its meaning and actions that go beyond the boundaries of individual, social experience in the form of higher meaningfulness, which is the specificity of myth. Attention is focused on a certain kind of interaction between myth and philosophy, where the myth, despite its irrational essence, has not been left out of the attention of philosophical thought. It is emphasized that mythology constantly experienced changes and adaptation to new living conditions, cultural factors and its paradigmatic foundations. But despite everything, from its critical understanding to its rehabilitation in postmodernism, the myth continues to play an important role in influencing human consciousness and shaping worldview. Being actually rehabilitated, the myth is considered as an important factor in the process of forming not only cultural symbols but also narratives. It complements rational knowledge, helps to understand archetypal and symbolic aspects of human reality, which are not always comprehended with the help of rational methods of cognition.